2003
DOI: 10.1016/s0885-3924(03)00219-7
|View full text |Cite
|
Sign up to set email alerts
|

Definitions related to the medical use of opioids: Evolution towards universal agreement

Abstract: Misunderstandings regarding the nature and occurrence of addiction have historically been barriers to the appropriate treatment of pain and have stigmatized the medical use of opioids. This article reviews the evolution of nomenclature related to addiction, presents current scientific understanding of addiction that may help shape universally acceptable terminology, and discusses an integrated effort of pain and addiction professionals to reach consensus on addiction-related terms. The article suggests key pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
142
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(148 citation statements)
references
References 41 publications
1
142
0
5
Order By: Relevance
“…In the current study, we were not able to determine whether aberrant opiate use was due to true addiction or pseudoaddiction since the latter may only be discerned through clinical intervention and observation (Savage et al 2003). Nevertheless, if pseudoaddiction were present, we would expect that both pain and aberrant opiate use would improve over time whereas pain-specific use would remain stable.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In the current study, we were not able to determine whether aberrant opiate use was due to true addiction or pseudoaddiction since the latter may only be discerned through clinical intervention and observation (Savage et al 2003). Nevertheless, if pseudoaddiction were present, we would expect that both pain and aberrant opiate use would improve over time whereas pain-specific use would remain stable.…”
Section: Discussionmentioning
confidence: 83%
“…Schieffer et al (2005) in the largest study to date reported that chronic pain patients with a history of substance abuse evidenced higher rates of medication misuse compared to those without such history despite equivalent levels of prescribed opiates and similar self-ratings of medication effectiveness. Lusher et al (2006) found that among patients with sickle cell disease, physiological dependence and illicit drug use were associated with true addiction to opiates (i.e., a primary neurobiological disease characterized by compulsive use despite harm and craving) (Heit 2001;Savage et al 2003) whereas disputes with staff about analgesics were associated with risk of pseudoaddiction (i.e., aberrant behaviors that resolve once pain is adequately treated).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant medication use incorporates a variety of behaviors commonly believed to be associated with opioid medication misuse, abuse, and addiction. 33 Since there is no gold standard for identifying which patients are and which are not abusing their prescription medications, 32 we classified patients into categories of aberrant medication-related behavior by triangulating three perspectives, selfreport via structured interview, physician report, and urine toxicology results. The ADBI is based on positive scores on 1) the self-reported PDUQ, 2) the physician-reported POTQ, and 3) the urine toxicology results.…”
Section: Evaluations Of the Beta Version Of The Soapp-r And Creation mentioning
confidence: 99%
“…39 White et al also conducted subgroup analyses to explore the potential for overlap between dependence and abuse, since dependence is neither a necessary nor sufficient characteristic of abuse or addiction. 40 In these sensitivity analyses, in which the investigators identified nonmutually exclusive subgroups of patients diagnosed either with abuse or with dependence or poisoning, persons in the abuse subgroup had total mean per-patient direct health care costs of $18,388, compared with $2,210 for a matched comparison group. 39 Per-patient costs in the dependence/poisoning group were $16,204, and matched comparison group subjects incurred costs of $2,179.…”
Section: Economic Burden Of Prescription Opioid Misuse and Abusementioning
confidence: 99%